Activation of the Organum Vasculosum of the Lamina Terminalis Produces a Sympathetically Mediated Hypertension. Issue 1 (January 2022) - Stocker, Sean D.; Wenner, Megan M.; Farquhar, William B.; Browning, Kirsteen N.
Abstract : Neurons in the organum vasculosum of the lamina terminalis (OVLT) sense extracellular NaCl and angiotensin II concentrations to regulate body fluid homeostasis and arterial blood pressure. Lesion of the anteroventral third ventricular region or OVLT attenuates multiple forms of neurogenic hypertension. However, the extent by which OVLT neurons directly regulate sympathetic nerve activity to produce hypertension is not known. Therefore, the present study tested this hypothesis by using a multi-faceted approach including optogenetics, single-unit and multifiber nerve recordings, and chemogenetics. First, optogenetic activation of OVLT neurons in conscious Sprague-Dawley rats (250–400 g) produced frequency-dependent increases in arterial blood pressure and heart rate. These responses were not altered by the vasopressin receptor antagonist (β-mercapto-β, β-cyclopentamethylenepropionyl1, O-me-Tyr2, Arg8)–vasopressin but eliminated by the ganglionic blocker chlorisondamine. Second, optogenetic activation of OVLT neurons significantly elevated renal, splanchnic, and lumbar sympathetic nerve activity. Third, single-unit recordings revealed optogenetic activation of the OVLT significantly increased the discharge of bulbospinal, sympathetic neurons in the rostral ventrolateral medulla. Lastly, chronic chemogenetic activation of OVLT neurons for 7 days significantly increased 24-hour fluid intake and mean arterial blood pressure. When the 24-hour fluid intake was clamped at baseline intakes, chemogenetic activation of OVLT neurons still produced a similar increase in arterial blood pressure. Neurogenic pressor activity assessed by the ganglionic blocker chlorisondamine was greater at 7 days of OVLT activation versus baseline. Collectively, these findings indicate that acute or chronic activation of OVLT neurons produces a sympathetically mediated hypertension. Abstract : Supplemental Digital Content is available in the text.